2009
DOI: 10.1021/je800637t
|View full text |Cite
|
Sign up to set email alerts
|

Solubility, Density, Viscosity, Refractive Index, and Electrical Conductivity for Potassium Nitrate−Water−2-Propanol at (298.15 and 313.15) K

Abstract: The solubility of potassium nitrate in aqueous 2-propanol solution has been determined at the temperatures of (298.15 and 313.15) K and atmospheric pressure. The densities, viscosities, refractive indices, and electrical conductivities of potassium nitrate in water and in the saturated solutions of aqueous 2-propanol were measured at these two temperatures. Solubilities were determined using the analytical gravimetric method. Densities were determined using a vibrating-tube densimeter. Viscosities were measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 10 publications
1
15
0
Order By: Relevance
“…This is due to the solubility of the salt at 35 C being greater than that at 25 C. And after the point of the intersection, temperature should be the key factor for the refractive index, which will be reduced when the temperature is raised. This phenomenon is different from that in the KNO 3 þ 2-propanol þ H 2 O system (Kao and Tu, 2009). For the KNO 3 þ 2-propanol þ H 2 O system, the refractive index decreased with an increase of the concentration of 2-propanol until w % 0.1 (298.15 K) and w % 0.2 (313.15 K).…”
Section: Resultsmentioning
confidence: 74%
See 1 more Smart Citation
“…This is due to the solubility of the salt at 35 C being greater than that at 25 C. And after the point of the intersection, temperature should be the key factor for the refractive index, which will be reduced when the temperature is raised. This phenomenon is different from that in the KNO 3 þ 2-propanol þ H 2 O system (Kao and Tu, 2009). For the KNO 3 þ 2-propanol þ H 2 O system, the refractive index decreased with an increase of the concentration of 2-propanol until w % 0.1 (298.15 K) and w % 0.2 (313.15 K).…”
Section: Resultsmentioning
confidence: 74%
“…Pena et al (1998) reported the apparent molar volumes of NaNO 3 þ H 2 O þ ethanol and KNO 3 þ H 2 O þ ethanol systems. The solubility, refractive index, density, electrical conductivity, and viscosity of KNO 3 þ H 2 O þ 2-propanol, NaNO 3 þ H 2 O þ poly (ethylene glycol), phenolic compounds þ aqueous alkali metal nitrate, NaNO 3 þ seawater have also been investigated (Graber et al, 2002;Kao and Tu, 2009;Noubigh et al, 2008;Pirahmadi and Behzadi, 2011;Taboada et al, 2012). More recently, Li et al (2011) reported the solubilities of LiNO 3 in organic solvents (methanol, ethanol, 1-propanol, 2-propane, and 1-butanol).…”
Section: Introductionmentioning
confidence: 99%
“…This is, however, completely different from the systems of NaCl/KCl + ethanol + H 2 O 5 and KNO 3 + propan-2-ol + H 2 O. 7 Moreover, the refractive indices of the systems almost overlapped, except for RbNO 3 + glycerol + H 2 O at low concentrations of glycerol. This can be explained by the two contrary factors that affect the refractive index of the systems.…”
Section: Density (ρ) and Refractive Index (N D ) For Systems Mno 3 (mentioning
confidence: 80%
“…Some researchers focused on the study of systems that include alkali nitrates. For example, reported were the solubility, refractive index, density, electrical conductivity and viscosity of NaNO 3 + H 2 O + poly(ethylene glycol), 6 KNO 3 + H 2 O + propan-2-ol, 7 and LiNO 3 in organic solvent (methanol, ethanol, propan-1-ol, propan-2--ol and butan-1-ol). 8 In previous work, our research groups have focused on the physical-chemical properties of rare alkali metal (Rb and Cs) salts + alcohol/PEG (polyethylene glycol) + water systems.…”
Section: Introductionmentioning
confidence: 99%
“…This separation process has several advantages compared to traditional methods of crystallization including increased yields, operation at ambient temperature, high purity of the product, and fitness for systems where the temperature has little effect on the solubility (Taboada et al, 2005;Kao and Tu, 2009;Pawar et al, 2009Pawar et al, , 2010. The main quality of the solvent is its capacity to generate supersaturation in the aqueous dissolution of the salt (Berry et al, 1997).…”
Section: Introductionmentioning
confidence: 99%